Analisis Stress Kerja Terhadap Kinerja Karyawan Bakso Haji Sony (Studi Kasus Cabang Wolter Monginsidi) - Arfan Pratama. SA, M.; Tiara Narundana, Vonny (CV. Lafadz Jaya, 2022)
In the development of research carried out to find out and analyze efforts to overcome work stress at Bakso Haji Sony. This examination is a type of subjective exploration, so the investigation of the information applied is spellbinding. Information sorting is an action to describe or collect all the information that has been obtained from the field as perception, encounter and information as a particular record no matter what. Show of information, an effort to introduce research data through data descriptions. Information reduction is the most common way of paying attention to the simplification, abstraction, and alteration of information in the field. End and check is to observe data in the field. Considering the hypothetical investigation and the consequences of examining the information, it tends to be concluded that: the three research subjects experienced job stress while working at Bakso Haji Sony. The stressor is different for each subject.